(Non-) robustness of vulnerability assessments to climate change: An application to New Zealand. (1st December 2017) - Fernandez, Mario Andres; Bucaram, Santiago; Renteria, Willington
Abstract: Assessments of vulnerability to climate change are a key element to inform climate policy and research. Assessments based on the aggregation of indicators have a strong appeal for their simplicity but are at risk of over-simplification and uncertainty. This paper explores the non-robustness of indicators-based assessments to changes in assumptions on the degree of substitution or compensation between indicators. Our case study is a nationwide assessment for New Zealand. We found that the ranking of geographic areas is sensitive to different parameterisations of the aggregation function, that is, areas that are categorised as highly vulnerable may switch to the least vulnerable category even with respect to the same climate hazards and population groups. Policy implications from the assessments are then compromised. Though indicators-based approaches may help on identifying drivers of vulnerability, there are weak grounds to use them to recommend mitigation or adaptation decisions given the high level of uncertainty because of non-robustness. Highlights: Vulnerability assessments based on indicators are not robust. Different aggregation assumptions lead to different policy implications. There is no ground to claim the superiority of an aggregation assumption over others. Policy implications from indicators-based approaches are misleading.